2020
DOI: 10.1192/bjo.2020.152
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for suicide in Bangladesh: case–control psychological autopsy study

Abstract: Background Suicide is an important, understudied public health problem in Bangladesh, where risk factors for suicide have not been investigated by case–control psychological autopsy study. Aims To identify the major risk factors for suicide in Dhaka, Bangladesh. Methods We designed a matched case–control psychological autopsy study. We conducted a semi-structured interview with the next-of-kin of 100 individuals who died by suicide and 100 living controls, matched for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…An estimated 10,000 suicide deaths occur in Bangladesh every year [ 63 ], although the exact number is likely higher given data and reporting challenges. Reasons for these deaths have focused broadly on the psychiatric disorder, physical disability, traumatic life events, economic hardship along with age, literacy rate, and place of residence (urban/rural) [ 18 , 64 ]. However, the focus on suicide in LMIC is considerably lower than in high-income countries, which contributes to a predominantly Western view theorising how and why suicide occurs while simultaneously not acknowledging the different risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 10,000 suicide deaths occur in Bangladesh every year [ 63 ], although the exact number is likely higher given data and reporting challenges. Reasons for these deaths have focused broadly on the psychiatric disorder, physical disability, traumatic life events, economic hardship along with age, literacy rate, and place of residence (urban/rural) [ 18 , 64 ]. However, the focus on suicide in LMIC is considerably lower than in high-income countries, which contributes to a predominantly Western view theorising how and why suicide occurs while simultaneously not acknowledging the different risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…There are thousands of clinical investigations in clinical autopsy that supports the major post-mortem diagnosis yet there are diagnostic errors in 30% cases. 8 The significant inconsistency decreasing over the period of time, though 4-7% cases nearly touch the discrepancies. 9 In the modern practices the autopsy usually indicates the detailed examination, an autopsy needs the careful medical examiners and staff to expand the deal of efforts to identify the unattended death cases, sudden death cases, unexpected deaths cases, and deaths due to traumas.…”
Section: Introductionmentioning
confidence: 94%
“…The relatives of the deceased mentioned that 47% of the suicides were related to sexual and marital issues mentioned as extramarital love relationship (12%), premarital love relationship (12%), sexual abuse (9%), quarrel with spouse (6%), being refused to marry by the lover (6%), and forceful marriage (2%). 3 Another previous casecontrol study also identified a love relationship and a quarrel with the spouse as risk factors for suicide. 4 The findings indicate a close relationship of psychosexual events with the suicides in Bangladesh, perhaps a sociocultural influence.…”
mentioning
confidence: 96%
“…Choice marriage was significantly found higher among suicides when compared to the age and sex‐matched living controls. The relatives of the deceased mentioned that 47% of the suicides were related to sexual and marital issues mentioned as extramarital love relationship (12%), premarital love relationship (12%), sexual abuse (9%), quarrel with spouse (6%), being refused to marry by the lover (6%), and forceful marriage (2%) 3 . Another previous case‐control study also identified a love relationship and a quarrel with the spouse as risk factors for suicide 4 …”
mentioning
confidence: 99%
See 1 more Smart Citation